Impact of infant massage on infant growth, development, and mother–infant interaction - Siti Rohmah; Triana Indrayani; Retno Widowati; Vivi Silawati (KHD-Production, 2026)
The prevalence of growth and developmental disorders among toddlers remains high, reaching 28.7%, and children experiencing early growth delays are at increased risk of developing non-communicable diseases such as diabetes and cardiovascular disorders later in life. Developmental delays that occur before age 20 may persist and affect long-term health outcomes. This study aimed to examine the impact of infant massage on growth, development, and mother–infant interaction among infants aged 6–12 months. A pre-experimental study with a pretest–posttest control group design was conducted. A total of 40 infants aged 6–11 months were recruited using total sampling and allocated into an intervention group (n = 20) and a control group (n = 20). Study instruments included the Bethlehem Mother–Infant Interaction Scale (BMIS), the Ages and Stages Questionnaire–Third Edition (ASQ-3), standardized infant massage procedures, observation sheets, weight scales, and length measurement tools. Data were analyzed using descriptive statistics and nonparametric inferential tests, including the Wilcoxon Signed Ranks Test for within-group comparisons and the Mann–Whitney U Test for between-group comparisons. The results demonstrated significant improvements in growth, developmental outcomes, and mother–infant interaction following infant massage in the intervention group. In contrast, no significant changes were observed in the control group across assessment periods. Significant differences were also identified between the intervention and control groups. In conclusion, infant massage is effective in enhancing growth, development, and mother–infant interaction among infants in Depok City. Training and educational programs on proper infant massage techniques are recommended for mothers to promote regular practice at home, strengthen emotional bonding, and support optimal infant development.